Yugoslav communists and European far-left - from first supporters of Italian Eurocommunists to last allies of French neo-stalinists (1965-1985) - Filipović Luka (Filozofija i Društvo, 2023)
Complex structural changes of social realty in SFRY and Western Europe during post-war decades have created the need for the largest Marxist parties of Europe outside Eastern Bloc to accommodate their party policies to new political challenges and social circumstances. Gradually, communist parties of Mediterranean started to contemplate creation of a new Marxist ideology for the welfare state era, which in practice meant seizing attempts to adjust principles of Bolshevik socialist model to their unique local circumstances, and moving away from the influence of Soviet party. League of Communists of Yugoslavia supported the reformist fractions of Italian, French, Greek and Spanish communist parties, which opened the path for further expansion of international influence and prestige of the Yugoslav communists. However, historical evolution of SFRY state policies and Yugoslav party ideology eventually took a different course than the reforms of party policies and ideologies of early Eurocommunist parties. The purpose of this article is to contribute to further understanding of the long term social and historical process which created a drift between the leading reformist parties of Europe. This is to be achieved by applying comparative method to the results of archival research conducted on historical sources that testify about the cooperation between Yugoslav, Italian and French communists at various time points during the twenty year long period, while using the findings of numerous historical, sociological and philosophical books and articles in order to bring the research results in the appropriate social and historical context.